BRAF V600E and TERT Promoter Mutations in Papillary Thyroid Carcinoma in Chinese Patients. - Jian Sun; Jing Zhang; Junliang Lu; Jie Gao; Xinyu Ren; Lianghong Teng; Huanli Duan; Yansong Lin; Xiaoyi Li; Bo Zhang; Zhiyong Liang (PLoS ONE, 2016)
BACKGROUND:The BRAF V600E and telomerase reverse transcriptase (TERT) promoter mutations have been reported in papillary thyroid carcinoma (PTC). The aim of this retrospective cross-sectional study was to add further information regarding the prevalence of the BRAF V600E and TERT promoter mutations in Chinese PTC and their clinicopathological associations. METHODS:We detected the BRAF V600E mutation and TERT promoter mutations in 455 Chinese PTC patients and analyzed the association of these mutations with several clinicopathological features. RESULTS:The BRAF V600E mutation was detected in 343 (75.4%) of 455 cases and was significantly associated with older age (p<0.001) and conventional subtype (p = 0.003). TERT promoter mutations were detected in 19 (4.4%) of 434 PTCs and were associated with older age (p<0.001), larger tumor size (p = 0.024), and advanced TNM stage(p<0.001). Of the 19 patients that were positive for TERT promoter mutations, 18 (94.7%) also harbored the BRAF V600E mutation. CONCLUSION:We determined the prevalence and clinicopathological associations of BRAF V600E and TERT promoter mutations in Chinese PTC patients. TERT promoter mutations but not the BRAF V600E mutation were associated with more advanced TNM stage upon diagnosis.